Ultrasound-guided Treatments for the Painful Shoulder - Papalexis, Nicolas; Ponti, Federico; Rinaldi, Raffaella; Peta, Giuliano; Bruno, Riccardo; Miceli, Marco; Battaglia, Milva; Marinelli, Alessandro; Spinnato, Paolo (Current Medical Imaging, 2022)
Shoulder pain is an extremely common condition. The painful shoulder may be the result of a wide spectrum of underlying pathological conditions, including calcific tendinopathy of the rotator cuff, subacromial-subdeltoid bursitis, acromioclavicular or glenohumeral arthritis, tenosynovitis of the long biceps tendon, rotator cuff lesions, and many other less common conditions. Ultrasound imaging is an effective tool for the diagnosis and also for the image guidance of treatment of the majority of these conditions. Several ultrasound-guided procedures are effective for pain relief, such as percutaneous irrigation, intra-bursal or intra-articular drugs injection, fluid aspiration, neural block. This review article aims to summarize and discuss the most common treatment possibilities with ultrasound guidance for the painful shoulder.
Keywords: shoulder pain